TELLING YOURSELF TO TRANSFORM YOU. Subversive perspectives to disabilty - Blas González; Moisés Mañas Olmo; Pablo Cortés González (Universidad Nacional del Nordeste, 2019)
School experiences are going to leave a mark in the perception and social construction that each person will have of the educational system, shaping the meaning which the school has had for them and for society, broadly speaking. Attending school is a significant experience, even more, when the students are exposed to violent and segregated practices, which in many cases they are spread to the family context with their identity, social and emotional consequences. Based on the life histories of two people diagnosed with Asperger's syndrome and two other people diagnosed with intellectual disability, we came to know and to analyze their school experiences from a established viewpoint. Through this essay, we are trying to approach an interpretative analysis of some critical school episodes which have shaped the identity of the participants.